Fetus in Fetu: Lessons Learned from a Large Multicenter Cohort Study - Taher, Heba M. A.; Abdellatif, Mostafa; Wishahy, Ahmed Mohamed Kadry; Waheeb, Saber; Saadeldin, Yasser; Kaddah, Sherif; Abdulsattar, Ayman Hussein; Osman, Mohamed Abdulkader; El Tagy, Gamal Hassan; Elbarbary, Mohamed M.; Khairi, Ahmad; Tawfik, Sherifa; Anis, Shady; Anis, Elia; Farouk, Moemn; Abdelfattah, Ahmed Hamdy; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2020)
Introduction Fetus in fetu (FIF) is an extremely rare condition of abnormal twinning during embryogenesis. Most publications are single case reports. We describe the combined experience of four large tertiary referral centers with FIF which were not previously reported or published, and thereby draw conclusions to establish criteria for the workup, diagnosis, and management including intraoperative risk.Materials and Methods A survey was forwarded to a national pediatric surgery group which includes members from all pediatric surgery centers in the country enquiring about unpublished cases of FIF encountered over a 20-year interval. The cohort was analyzed for age of presentation, type of presentation, diagnostic workup, surgical management, and outcome.Results From 1998 to 2018, a total of 10 FIF cases were included in the study. Mean age of presentation was 4 months. Computed tomography and ultrasound were the main preoperative diagnostic modality in our cohort. Resection of the mass was curative in nine cases. Two cases in which the FIF was in direct topographic proximity to the biliary tree suffered severe intraoperative or lethal postoperative complications.Conclusion Complete excision of FIF is the treatment of choice and generally results in excellent long-term quality of life. Mortality is rare and may be associated with biliary involvement and retroperitoneal right upper quadrant location of the FIF tends to be associated with increased risk in excision, and there is also a possible association with the presence of immature elements in the pathology report.
Keywords: fetus in fetu; retroperitoneal; teratoma